Populations of Antarctic hairgrass (Deschampsia antarctica) show low genetic diversity - Holderegger, R; Stehlik, I; Smith, R I L; Abbott, R J (2003)
Populations of the only two flowering plants native to the Antarctic have recently increased in number and size possibly due to climate warming. We have undertaken a preliminary study of the population genetics of one of these species by surveying variation in amplified fragment length polymorphisms (AFLP) within the Antarctic Hairgrass, Deschampsia antarctica. Populations of D. antarctica from two widely separated regions of the maritime Antarctic, namely Signy Island in the north and Leonie Islands 1350 km farther south, were characterized by low genetic diversity (only 15.95% of total genetic variation found within populations). Populations from the northern and southern maritime Antarctic were genetically distinct from each other (F-CT = 37.10%), and low levels of historical gene flow occurred among them (Nm = 0.05). This genetic structure suggests that new populations of D. antarctica are founded by one or few individuals, which mainly reproduce by self-fertilization and/or vegetative propagation. Vegetative reproduction and selfing are, therefore, likely to have been key factors in the establishment of D. antarctica at new sites in the Antarctic during recent years.